Relation between low back pain and physical characteristics in high school male soccer players - Ryota Tejima; Yasushi Fukuda; Tatsuhiko Yamaguchi; Koji Koyama (Japanese Society of Physical Fitness and Sports Medicine, 2021)
Studies have shown that soccer players have a high prevalence of low back pain (LBP). However, physical characteristics (sagittal spinal alignment and hip joint range of motion [ROM]) associated with LBP have not been clarified. This study seeks to clarify the relationship between physical characteristics and LBP in high school male soccer players. The participants were 90 high school male soccer players. The presence of LBP was evaluated using a questionnaire. We assigned the participants into two groups: the non-LBP group (n = 58) and the LBP group (n = 32). Passive ROM of hip and sagittal spinal alignment were measured. Thoracic kyphotic angle (TKA) was significantly higher in the LBP group than in the non-LBP group, and the ROM of hip joint extension in the nondominant leg was significantly lower in the LBP group than in the non-LBP group. On logistic regression analyses, TKA in the upright position (adjusted odds ratio [OR]: 1.087, 95% confidence interval [CI]: 1.019-1.159, p < 0.01) and hip extension ROM deficits in the nondominant leg (adjusted OR: 0.888, 95% CI: 0.789-0.999, p < 0.05) were related to LBP in high school male soccer players as determined. This study suggests that hyperkyphosis in the upright position and hip extension ROM deficits in the nondominant leg were related to LBP in high school male soccer players.